Home bias in global bond and equity markets: the role of real exchange rate volatility - Michael Fidora; Marcel Fratzscher; Christian Thimann (European Central Bank (ECB), 2006)
This paper focuses on the role of real exchange rate volatility as a driver of portfolio home bias, and in particular as an explanation for differences in home bias across financial assets. We present a Markowitz-type portfolio selection model in which real exchange rate volatility induces a bias towards domestic financial assets as well as a stronger home bias for assets with low local currency return volatility. We find empirical support in favour of this hypothesis for a broad set of industrialised and emerging market countries. Not only is real exchange rate volatility an important factor behind bilateral portfolio home bias, but we find that a reduction of monthly real exchange rate volatility from its sample mean to zero reduces bond home bias by up to 60 percentage points, while it reduces equity home bias by only 20 percentage points.
Keywords: F30; F31; G11; G15; 330; capital flows; Exchange rate volatility; global financial markets; home bias; portfolio investment; risk; Kaufkraftparität; Volatilität; Portfolio-Management; Kapitalmobilität; Theorie; Schwellenländer; Industrieländer